2020
DOI: 10.1055/s-0039-3399559
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jiroveci

Abstract: Pneumocystis jiroveci remains an important fungal pathogen in a broad range of immunocompromised hosts. The natural reservoir of infection remains unknown. Pneumocystis jiroveci Pneumonia (PJP) develops via airborne transmission or reactivation of inadequately treated infection. Nosocomial clusters of infection have been described among immunocompromised hosts. Subclinical infection or colonization may occur. Pneumocystis pneumonia occurs most often within 6 months of organ transplantation and with intensified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 167 publications
1
37
0
4
Order By: Relevance
“…Patienten mit einer zellulären Immunschwäche tragen ein erhöhtes Risiko, eine symptomatische Pneumocystis-Infektion zu entwickeln. Vor dem routinemäßigen Einsatz der PCP-Prophylaxe erkrankten häufig HIV-infizierte mit einer fortgeschrittenen Immundefizienz mit CD4-Zellen von < 200/µl [5]. Die PCP scheint auch bei HIV-negativen Patienten in der Mehrzahl der Fälle an ein zelluläres Immundefizit mit einer deutlichen Erniedrigung der CD4-Zellen gebunden zu sein [16], wobei der klinische Verlauf bei Nicht-AIDS-Patienten häufig schwerer zu sein scheint [8].…”
Section: Diskussionunclassified
See 3 more Smart Citations
“…Patienten mit einer zellulären Immunschwäche tragen ein erhöhtes Risiko, eine symptomatische Pneumocystis-Infektion zu entwickeln. Vor dem routinemäßigen Einsatz der PCP-Prophylaxe erkrankten häufig HIV-infizierte mit einer fortgeschrittenen Immundefizienz mit CD4-Zellen von < 200/µl [5]. Die PCP scheint auch bei HIV-negativen Patienten in der Mehrzahl der Fälle an ein zelluläres Immundefizit mit einer deutlichen Erniedrigung der CD4-Zellen gebunden zu sein [16], wobei der klinische Verlauf bei Nicht-AIDS-Patienten häufig schwerer zu sein scheint [8].…”
Section: Diskussionunclassified
“…Die Infektion kommt häufiger auch während Neutropenien bzw. niedrigen Lymphozytenzahlen, bei einer Hypogammaglobulinämie und im Verlauf einer Zytomegalievirusinfektion (CMV) vor [5,8,9]. Die klassische Symptom-Trias besteht aus trockenem Reizhusten, subfebrilen Temperaturen und einer langsam progredienten Belastungsdyspnoe [5,8,9].…”
Section: Diskussionunclassified
See 2 more Smart Citations
“…Pneumocystosis is an opportunistic infection caused by Pneumocystis jirovecii fungus that is common in immunocompromised patients and can occur in indi-Open Journal of Nephrology viduals with impaired innate immunity through corticosteroids, CMV infection, or lack humoral or cellular immune functions [6]. One study showed that up to one in five people may have Pneumocystis jirovecii DNA in the bronchoalveolar lavage fluid [7], thus suggesting the possibility of reactivating a previously established infection as being a potential cause of disease in susceptible hosts, such as in the case of kidney transplanted recipients.…”
Section: Introductionmentioning
confidence: 99%